PENGARUH EMPLOYEE EMPOWERMENT DAN BUDAYA ORGANISASI TERHADAP KOMITMEN ORGANISASI KARAYAWAN HOTEL FURAYA PEKANBARU DENGAN MOTIVASI SEBAGAI VARIABEL INTERVENING - Dewi, Margie; Indarti, Sri; Rifqi, Ahmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The purpose of this research is to knowing the effect of employee empowerment and organization culture on commitment organization employee of Furaya Hotel Pekanbaru with motivation as intervening variable. In this research consist of two dependent variables and two independent variables. These variables are commitment organization (Y2), Motivation (Y1), Employee Empowerment (X1) and Organization Culture (X1). The research used 124 respondents as samples whom taken from 11 department of Furaya Hotel Pekanbaru. The research used descriptive method which gave questionnaire to respondents. From analyze data used path analyze with SPSS (Service for Product and Statistic Solution). The result of the research show that partially employee empowerment (X1) with value t hitung 3,510 , organization culture (X2) with value t hitung 7,783 positively and significantly took effect to commitment organization (Y1). Partially also concluded that motivation (Y1) with value t hitung 2,814 took effect positively and significantly to commitment organization (Y2). The effect of employee empowerment to commitment organization through motivation is 7,161. The effect of organization culture to commitment organization through motivation is 8,932. So that concluded employee empowerment (X1) and organization culture (X2) took effect positively and significantly to commitment organization (Y2) of Furaya Hotel Pekanbaru employee through motivation (Y1) as intervening variable.   Keywords: commitment organization, motivation, employee empowerment, organizational culture.